Accu Scrap Raw Material Inventorycontrol Using the Min- Max Method: Pengendalian Persediaan Bahan Baku Scrap Accu Dengan Metode Min-Max - Faizin, Muhammad Nur; Jakaria, Ribangun Bamban (Procedia of Engineering and Life Science, 2024)
This research investigates the efficacy of implementing the Min-Max method to enhance inventory control performance in a manufacturing setting converting ACCU scrap into tin metal. Focused on two product types, bullion, and ingots, the study aims to optimize inventory policies by determining safety stock, minimum and maximum stock levels, order quantities, and reorder points to mitigate stockouts and overstocks. Results demonstrate a significant improvement, with the Min-Max method enabling a 33% increase in raw material control effectiveness compared to previous methods. This research underscores the potential for the Min-Max approach to provide practical solutions for inventory management challenges in manufacturing, offering valuable insights for industry practitioners and researchers alike. Highlight : The Min-Max method improved inventory management effectiveness by 33%. This approach facilitated the determination of safe stock levels, minimal order quantities, and reorder points. Manufacturers experienced reduced operating expenses while maintaining competitive edge and responsiveness to market dynamics. Keywords: Accu scrap processing, Min-Max method, inventory control, supply chain optimization, resource allocation